KOMODIFIKASI AGAMA DALAM IKLAN SAFI SKINCARE - Munib, Abd (UIN Sumatera Utara Medan, 2024)
This scientific article discusses the symbols in advertisements which indicate an element of intent to make religious values a selling point (commodification). Advertising is one of the persuasive communication media that is deliberately made to attract audiences with the aim of obtaining economic benefits or benefits. The advertisements referred to in this study are advertisements for beauty products with the Safi brand, which are quite popular among Muslim women in Indonesia. Advertisers will do anything to make their products sell well in the market, including the practice of commodification. In this case, religion has changed its function to become an exchange value for material interests. The method used in this paper is qualitative-interpretative. The analytical knife used is Charles Sander Peirce's semiotics which is known as the triadic relation (object, interpretant, and representament). The results of this study indicate that symbols such as the selection of Muslim women actors are marked by the clothes used, friendly attitudes, smiles, thoroughness shown by the actors, the setting that reflects cleanliness, product taglines, and the halal label from MUI change religious values to no more than traded value.